2014
DOI: 10.1021/jm5000547
|View full text |Cite
|
Sign up to set email alerts
|

Strategies To Inhibit Tumor Associated Integrin Receptors: Rationale for Dual and Multi-Antagonists

Abstract: The integrins are a family of 24 heterodimeric transmembrane cell surface receptors. Involvement in cell attachment to the extracellular matrix, motility, and proliferation identifies integrins as therapeutic targets in cancer and associated conditions: thrombosis, angiogenesis, and osteoporosis. The most reported strategy for drug development is synthesis of an agent that is highly selective for a single integrin receptor. However, the ability of cancer cells to change their integrin repertoire in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 146 publications
0
108
0
Order By: Relevance
“…EETI 2.5F is unique in its ability to target a broad spectrum of tumor-associated integrins, a feature that has not been achieved with any antibody to date, which instead only bind av-containing integrins or a5b1 integrin. Targeting multiple integrin receptors is potentially beneficial for reducing drug resistance and tumor growth, as cancer cells can change their integrin repertoire in response to drug treatment (36). Integrins, particularly a6b4, a6b1, avb5, a2b1, and a3b1 (21), are found to be present on epithelial tissues and are also upregulated in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…EETI 2.5F is unique in its ability to target a broad spectrum of tumor-associated integrins, a feature that has not been achieved with any antibody to date, which instead only bind av-containing integrins or a5b1 integrin. Targeting multiple integrin receptors is potentially beneficial for reducing drug resistance and tumor growth, as cancer cells can change their integrin repertoire in response to drug treatment (36). Integrins, particularly a6b4, a6b1, avb5, a2b1, and a3b1 (21), are found to be present on epithelial tissues and are also upregulated in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Since the cyclic RGD peptides, such as c(RGDfK), are antagonists for α v β 3 and α v β 5 integrins, 4,3639,62 it is reasonable to believe that bioconjugates FITC-RGD 2 , FITC-3P-RGD 2 , and FITC-Galacto-RGD 2 will target both integrin α v β 3 and integrin α v β 5 . We were interested in dimeric cyclic RGD peptides because they have significantly higher integrin α v β 3 /α v β 5 binding affinity than their monomeric analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have shown that cancer cells change their integrin repertoire in response to drug treatment (Sheldrake and Patterson, 2014). Given the link between integrin expression and CYP3A4 activity illustrated here, integrin receptors may play a notable role in the development of drug resistance.…”
Section: Discussionmentioning
confidence: 77%
“…The diversity in these processes suggests that pathology of cancer as well as other noninfectious diseases in which integrins play a role (e.g., cardiovascular disease, diabetes, and wound healing) may not be attributed to a single integrin receptor, but instead are the end result of crosstalk between several integrin receptors. Thus, drugs targeting single as well as multiple integrin receptors have been developed for treatment of cancer and other diseases (Desgrosellier and Cheresh, 2010;Sheldrake and Patterson, 2014). In this context, data generated in our studies suggest that hepatic drug metabolism patterns can be significantly altered in response to these medications, which will most likely be given with other chemotherapeutic agents that are metabolized by CYP3A4, resulting in either an enhanced therapeutic effect or severe toxicities due to accumulation of unmetabolized by-products over time.…”
Section: Discussionmentioning
confidence: 91%